A Narrative Review on the Impact of School-Based Nursing on Adolescent Health Promotion and Public Health Outcomes - Alanazi, Hazzaa Bandar Hazzaa; Emad Souleman Ebani; Haya Mohammed Alrugaib; Alanoud Rodayen Eid Alharthi; Khawlah Khalid Al saloom; Fattemah Maber Yahya Al-Ribhi; Amani Raji Jaber AlRoyli; Ali Mohammed Ali Al Sheban; Aishah hassan Ali; Reem yati Alrasheedi; et al. (Saudi Journal of Medicine and Public Health, 2024)
<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Adolescence is a critical developmental period characterized by significant physical, cognitive, and emotional changes, during which lifelong health behaviors are established. School-based health centers (SBHCs) and school nursing represent a vital public health strategy to deliver accessible, preventive, and acute care to this often-underserved population. With rising rates of adolescent mental health crises, chronic conditions, and health inequities, the role of the school nurse has evolved far beyond basic first aid. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This narrative review synthesizes the evidence on the impact of school-based nursing models on direct adolescent health promotion and broader public health outcomes, examining effectiveness, implementation challenges, and return on investment. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A systematic literature search was conducted across PubMed, CINAHL, ERIC, PsycINFO, and Scopus. Peer-reviewed studies, systematic reviews, and policy reports published between 2010-2023 were analyzed thematically to evaluate outcomes related to clinical care, health behaviors, academic performance, and community health. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Evidence demonstrates that robust school nursing significantly improves immunization compliance, chronic disease management (e.g., asthma, diabetes), mental health screening and referral, and reproductive health access. Outcomes include reduced absenteeism, emergency department visits, and hospitalizations, alongside improvements in health literacy and self-management skills. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> School-based nursing is a highly effective, multi-sectoral intervention for advancing adolescent and public health. Sustained investment, standardized outcome metrics, and integration with primary care and mental health systems are essential to maximize its population health impact.